EMT FRAMEWORK PROPAGATING BEYOND ITS BORDERS: THE CONGRUENCE WITH NON-EUROPEAN PROFESSIONAL TRANSLATORS’ NEEDS - Esfandiari, Mohammad Reza (2017)
Intercultural communication has escalated social demand for translator training programs which has led to attempts to provide a proper educational basis for translator training. There is also a general agreement among scholars that there should be reconciliation between training and the actual translation world and the market. The EMT (European Master's in Translation) Competences Framework is the most comprehensive framework and is an improvement to previous models focusing on practice-oriented dimensions. However, this framework has been developed based primarily on the requirements of European professional translators. This study was conducted to look into the compatibility of the EMT framework with the needs of non-European professional translators. To this end, a total number of 177 participants from 34 nationalities and 21 languages participated in a questionnaire survey that explored the compatibility of the EMT framework competences with the needs of non-European professional translators. The results indicated that the most compatible components with non-European professional translators are the language, thematic, intercultural, translation service provision, information mining, and technological competences. The results obtained can provide insight for translator training program planners.